Morphology, growth, photosynthesis and pigments in Laminaria ochroleuca (Laminariales, Phaeophyta) under ultraviolet radiation - Roleda, Michael Y. (Animo Repository, 2004)
Young sporophytes of Laminaria ochroleuca were exposed in the laboratory either to a full light spectrum or to light depleted of only ultraviolet-B radiation (UVB) or of the whole ultraviolet radiation (UVR) using cutoff glass filters. The plants were grown under 16:8 h light-dark cycles with 6 h additional UV exposure in the middle of the light phase. Effective quantum yield of photosystem II (ΔF/Fm′) was measured daily, 1 h before UV exposure, at 2 and 5 h cumulative UV exposure and at 1 and 4 h after UV exposure. Growth was measured using two methods in separate experiments. In the first, a scanner with image analysis software was used to measure surface area every 3 days for 4 weeks. In the second, a growth chamber with online video measuring technique was used to measure growth every 10 min for 2 weeks. Pigments were measured at the end of the experiments. During the first day of UV exposure, the photosynthetic yield of plants exposed to photosynthetically active radiation (PAR) + ultraviolet-A radiation (UVA) and PAR + UVA + UVB was significantly reduced but was able to recover 1 h after the end of UV exposure. An increasing mean ΔF/Fm′ during UV exposure showed partial acclimation of photosynthesis in young sporophytes in the course of several days. However, a higher growth rate was observed in plants exposed to PAR alone, whereas reduced growth and damaged tissue were observed in plants exposed to UVR. Similarly, a lower content of all pigments was measured in thalli exposed to PAR + UVR. The result shows that acclimation of photosynthesis could underestimate the negative effect of this stress factor. Growth, as an integrative process, is a better parameter to explain ecophysiological performance at organism level. It was shown that growth and morphology of young sporophytes of L. ochroleuca are susceptible to UV damage, which could effectively limit the upper distributional range of this species.